Magnitude and antimicrobial susceptibility profile of bacteria isolated from pediatric sepsis cases at University of Gondar Hospital, Northwest Ethiopia - Gashaw Amsalu; Feleke Moges; Geta Bayu; Baye Gelaw (BMC, 2024)
Abstract Background Sepsis is one of the major causes of morbidity and mortality among pediatric patients throughout the world. The varying microbiological pattern of sepsis warrants the need for researches on the causative organisms and their antimicrobial susceptibility pattern. The epidemiology of neonatal and pediatric sepsis in Ethiopia is under-research. The objective of this study was to evaluate the burden of bacterial pathogens and their antimicrobial susceptibility patterns among children suspected of sepsis. Methods An institutional-based prospective cross-sectional study was conducted on 370 pediatric(age birth-15 years) patients suspected of sepsis at the University of Gondar Comprehensive Specialized hospital from December 2020 to November 2021. Blood samples were collected aseptically and inoculated into Tryptone Soya Broth for culture. The organisms grown were identified by standard microbiological methods and subjected to antibiotic susceptibility testing by modified Kirby-Bauer disk diffusion method recommended by Clinical laboratory and standard institute. Methicillin resistance was confirmed using Cefoxitin disk diffusion method. Data entry and analysis were done using Statistical Package for Social Sciences (SPSS) version 26 software. A p-value less than 0.05 at 95% confidence interval was considered statically significant. Results Out of the total 370 study subjects, 21.6% (80/370) of them were culture positive. Of these, 43 (53.8%) and 37 (46.3%) were Gram-positive and Gram-negative bacterial pathogens, respectively. The most prevalent Gram-positive bacterial isolate was Staphylococcus aureus (n = 24; 30%) and coagulase negative staphylococci (n = 7; 8.8%). Among the Gram-negative bacterial isolates, the leading bacteria was Klebsiella pneumoniae (n = 20; 25%) followed by Escherichia coli (n = 7; 8.8%). Clindamycin, Chloramphenicol, Gentamicin and Ciprofloxacin were the most effective antibiotics against Gram-positive bacterial isolates while Amikacin, Meropenem and Chloramphenicol were effective against Gram-negative pathogens. Methicillin resistance was detected in 45.8% of Staphylococcus aureus. Multi-drug resistance (MDR) antimicrobial susceptibility pattern was observed in 76% of the bacterial isolates. Conclusion Gram positive bacteria were the predominant isolates among pediatric sepsis cases and most of the bacterial isolates showed MDR. Staphylococcus aureus and Klebsiella pneumoniae were frequently isolated bacteria. The high prevalence of drug resistance warrants rational use of antibiotics and the need for regular antibiotic susceptibility surveillance studies.